2011
DOI: 10.1038/onc.2011.176
|View full text |Cite
|
Sign up to set email alerts
|

Role of connexin43 and ATP in long-range bystander radiation damage and oncogenesis in vivo

Abstract: Ionizing radiation is a genotoxic agent and human carcinogen. Recent work has questioned long-held dogmas by showing that cancer-associated genetic alterations occur in cells and tissues not directly exposed to radiation, questioning the robustness of the current system of radiation risk assessment. In vitro, diverse mechanisms involving secreted soluble factors, gap junction intercellular communication (GJIC) and oxidative metabolism are proposed to mediate these indirect effects. In vivo, the mechanisms behi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 25 publications
3
47
1
Order By: Relevance
“…Although the mechanisms underlying the RIBE are not fully understood, gap-junction intercellular communication [3,4] and the secretion of soluble factors from irradiated cells to the bystander cells were found to play important roles [5,6]. Reactive oxygen species (ROS), which were generated from irradiated cells, were among the reported bystander signals, which could lead to oxidative stress and DNA damage in nearby unirradiated cells.…”
Section: Definition and History Of The Ribementioning
confidence: 99%
“…Although the mechanisms underlying the RIBE are not fully understood, gap-junction intercellular communication [3,4] and the secretion of soluble factors from irradiated cells to the bystander cells were found to play important roles [5,6]. Reactive oxygen species (ROS), which were generated from irradiated cells, were among the reported bystander signals, which could lead to oxidative stress and DNA damage in nearby unirradiated cells.…”
Section: Definition and History Of The Ribementioning
confidence: 99%
“…5,47,48) In addition, a recent study has suggested the involvement of both Cx43 and ATP in long-range bystander radiation damage and oncogenesis in vivo. 49) However, the relationship between Cx43 and ATP in the bystander effect was unknown.…”
Section: )mentioning
confidence: 99%
“…Our results provide a novel insight into the mechanisms of ATP release induced by irradiation. 18,23) Since a radiation-induced bystander effect mediated by both ATP and Cx43 has been suggested in vivo, 49) recognition of the importance of ATP in this radiation-induced biological effect is now increasing.…”
Section: +mentioning
confidence: 99%
“…Transmission of radiationinduced signals between irradiated cells and adjacent non-irradiated cells might cause generation of reactive oxygen/nitrogen species in the nonirradiated cells, which might promote tumorigenesis. This is called as "by stander effect" and the mechanisms underlying bystander effect are not well defined, however some cytokines and/or intercellular gap junctions are considered responsible (25)(26)(27).…”
Section: Cns Radiation Therapymentioning
confidence: 99%